Management of a large atrial septal occluder embolized to the left ventricular outflow tract without the use of cardiac surgery. Issue 3 (31st January 2014) - Loh, Joshua P.; Satler, Lowell F.; Slack, Michael C.
<x xml:space="preserve">Abstract</x> Transcatheter closure of secundum‐type atrial septal defects (ASDs) using the AMPLATZER™ Septal Occluder (ASO) has been in use for more than a decade since its US Food and Drug Administration approval in 2001. Device embolization remains an uncommon complication, which can sometimes occur after the initial deployment. Previous reports of ASO devices embolized to the left ventricle have primarily been managed by open‐heart surgical retrieval. We present a case of an ASO device embolized to the left ventricular outflow tract (LVOT) 18 hr after initial implantation, which was successfully retrieved percutaneously, followed by successful closure of the ASD using a larger device. © 2014 Wiley Periodicals, Inc.